The contribution of narrative drawing in early literacy - Pitri, Eliza; Michaelidou, Antonia (Frontiers in Education, 2025)
In literate societies of the 21st century, written language plays a crucial role in both the professional and social life of individuals. Consequently, educational reforms emphasize the development of literacy skills in children. The ability to read and comprehend text is fundamental for individuals to fully engage and succeed in social contexts. Existing research supports that reading and writing are active cognitive processes essential for understanding and producing messages, and that there is a direct connection between children’s drawing and speech. Based on the above, a descriptive case study took place to look for evidence and provide examples of how a preschool child’s narrative drawings relate to early literacy skills. Narrative drawings are defined as sketches that are accompanied by a story told by a child while drawing or when presenting the final artwork. This study analyzed 35 narrative drawings, produced by a child between her four-and-a half and fifth year of age. The accompanying stories were recorded and transcribed for analysis purposes. Qualitative content analysis of both the drawings and the transcribed narratives provided evidence that narrative drawing promotes children’s reading readiness and offers opportunities for early literacy development.